Productivity, Wages, and the Balance of Payments - Laursen, Svend (The Review of Economics and Statistics, 1955)
IN the postwar discussions of the dollar problem, a number of writers have pointed to differences in national rates of productivity growth as one of the factors which has contributed to the imbalance in the world economy. It is the purpose of the present paper to study the validity of this argument. Clearly, such a study cannot be undertaken without including some consideration of relative movements of money wages. To use a shorthand expression, a country's competitive position in the world economy is, with given exchange rates, determined by the ratio between its productivity and its money wage rates. Consequently, both of these factors must be dealt with explicitly. The discussion of money wages will be undertaken from two points of view. In the first place, we shall analyze different norms for monetary and wage policies under conditions of divergent rates of productivity growth. Secondly, we shall discuss briefly whether the postwar commitments to a full employment policy in a number of countries have introduced a new element into the situation.